Effect of intrapartum pethidine on the neonatal outcome: is it duration related? - Abdulwahab, Dalia F; Husin, Roziah; Rukaia, Busurerah; Awang, Mokhtar; Ismail, Rozihan (Elsevier BV, 2012)
Objectives: To study the effect of pethidine on the intrapartum fetal heart rate (FHR) pattern and to assess the neonatal outcome with regards to the interval between pethidine administration to delivery of the fetus. Materials: 73 healthy women intrapartum from labour suite hospital Tengku Ampuan Afzan, Kuantan, Malaysia. Methods: This is a prospective observational study done on 73 healthy consented women with singleton pregnancy at term. All fetus were normal, vertex presentation with reactive FHR tracing before pethidine administration. FHR recording were performed for 40 minutes prior to and one hour post pethidine. Cervical dilatation of all patients ≤4cm at time of pethidine administration. Intramuscular pethidine 1 mg/kg was given as an intrapartum analgesia. The study sample was divided into two groups, first group delivered within 4 hours and second group delivered more than 4 hours after the pethidine administration. The data were analysed by SSPS 17.0. Results: the mean age of the recruited patients is 28.15±6.15 years and mean gestational age of 39.14±1.094 weeks. The mean duration from pethidine administration to delivery is 296.48±173.65 minutes (4 hours and 56 minutes). Four (5.5%) cases had suspicious CTG 1 hour post pethidine, 1 with absence of acceleration for 45 minutes and 3 cases with early deceleration lasted for 60 to 90 minutes. Out of 73 patients, 38 babies delivered within 4 hours and 35 delivered after 4 hours of pethidine. All neonates delivered with good Apgar Score (AS), 8 at 1 minute and 9 at 5 minute except 1 with AS of 5 at 1 min and 7 at 5 min which delivered more than 4 hours after pethidine. Sixteen (21.9%) cases were admitted to the Neonatal Intensive Care Unit (NICU). Eleven (68.75%) cases were admitted due to neonatal sedation from the delivery group less than 4 hours after pethidine. Five (31.25%) cases from the delivery group more than 4 hours, 4 cases with a diagnosis of transient tachypnea of newborn and 1 secondary to meconium aspiration syndrome (MAS). All discharge to mother after 24 hours, non required ventilation apart from the one with MAS which required ventilation for one day and longer admission. Despite of the higher number of those require admission in the less than 4 hours group, it was not statistically significant with P value of 7.44. Conclusions: Pethidine can be used as an intrapartum analgesia which is safe, easily available without major effect on fetal heart rate pattern and neonatal outcome even if given in advance stage of labour.